1999
DOI: 10.1074/jbc.274.45.32204
|View full text |Cite
|
Sign up to set email alerts
|

A Novel NE-dlg/SAP102-associated Protein, p51-nedasin, Related to the Amidohydrolase Superfamily, Interferes with the Association between NE-dlg/SAP102 and N-Methyl-d-aspartate Receptor

Abstract: The membrane-associated guanylate kinase proteins have been known to interact various membrane receptors with their N-terminal segments designated the PDZ domains and to cluster these receptors at the target site of the cell membrane. NE-dlg/SAP102, a neuronal and endocrine tissue-specific MAGUK family protein, was found to be expressed in both dendrites and cell bodies in neuronal cells. Although NE-dlg/SAP102 localized at dendrites was shown to interact with N-methyl-D-aspartate receptor 2B via the PDZ domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…As seen in Figure 1D, 72 hours is the minimum time of BDNF exposure needed to see the increase in cypin expression. It should be noted that cypin levels increase as neurons mature in culture (Kuwahara et al, 1999), and thus, we observed this baseline increase in cultures treated with DMSO. Thus, we used a 72 h incubation time for the rest of our studies, acknowledging the fact that we are studying pathways involved in longer term exposure to BDNF rather than a short pulse of BDNF exposure.…”
Section: Resultsmentioning
confidence: 55%
“…As seen in Figure 1D, 72 hours is the minimum time of BDNF exposure needed to see the increase in cypin expression. It should be noted that cypin levels increase as neurons mature in culture (Kuwahara et al, 1999), and thus, we observed this baseline increase in cultures treated with DMSO. Thus, we used a 72 h incubation time for the rest of our studies, acknowledging the fact that we are studying pathways involved in longer term exposure to BDNF rather than a short pulse of BDNF exposure.…”
Section: Resultsmentioning
confidence: 55%
“…Our results demonstrated that the 3′-UTR of DLG3 gene were a potential target of miR-1246. DLG3 is the first XLMR gene and is linked directly to NMDA receptor-mediated signaling and synaptic plasticity [63], [64]. Compared with the classical transcription factors, miR-1246 directly targeted the 3′-UTR of DLG3 mRNA ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…SAP102 also binds the PDZ region of other transmembrane proteins, such as the NMDA NR2 subunit (Lau et al . 1996) and nedasin S (Kuwahara et al . 1999), suggesting that it may bind NrCAM in a similar manner.…”
Section: Discussionmentioning
confidence: 99%